Memory load modulates graded changes in distracter filtering - Shimi, Andria; Woolrich, Mark W.; Mantini, Dante; Astle, Duncan E. (Frontiers in Human Neuroscience, 2015)
Our ability to maintain small amounts of information in mind is critical for successful performance on a wide range of tasks. However, it remains unclear exactly how this maintenance is achieved. One possibility is that it is brought about using mechanisms that overlap with those used for attentional control. That is, the same mechanisms that we use to regulate and optimise our sensory processing may be recruited when we maintain information in visual short-term memory (VSTM). We aimed to test this hypothesis by exploring how distracter filtering is modified by concurrent VSTM load. We presented participants with sequences of target items, the order and location of which had to be maintained in VSTM. We also presented distracter items alongside the targets, and these distracters were graded such that they could be either very similar or dissimilar to the targets. We analysed scalp potentials using a novel multiple regression approach, which enabled us to explore the neural mechanisms by which the participants accommodated these variable distracters on a trial-to-trial basis. Critically, the effect of distracter filtering interacted with VSTM load; the same graded changes in perceptual similarity exerted effects of a different magnitude depending upon how many items participants were already maintaining in VSTM. These data provide compelling evidence that maintaining information in VSTM recruits an overlapping set of attentional control mechanisms that are otherwise used for distracter filtering.